Associations between antenatal and perinatal risk factors and cerebral palsy: a Swedish cohort study. Issue 8 (7th August 2020) - Jöud, Anna; Sehlstedt, Andréa; Källén, Karin; Westbom, Lena; Rylander, Lars
Abstract : Objectives: To investigate known and suggested risk factors associated with cerebral palsy in a Swedish birth cohort, stratified by gestational age. Setting: Information on all births between 1995 and 2014 in Skåne, the southernmost region in Sweden, was extracted from the national birth register. Participants: The cohort comprised a total of 215 217 children. Information on confirmed cerebral palsy and subtype was collected from the national quality register for cerebral palsy (Cerebral Palsy Follow-up Surveillance Programme). Primary and secondary outcome measures: We calculated the prevalence of risk factors suggested to be associated with cerebral palsy and used logistic regression models to investigate the associations between potential risk factors and cerebral palsy. All analyses were stratified by gestational age; term (≥37 weeks), moderately or late preterm (32–36 weeks) and very preterm (<32 weeks). Results: In all, 381 (0.2 %) children were assigned a cerebral palsy diagnosis. Among term children, maternal preobesity/obesity, small for gestational age, malformations, induction, elective and emergency caesarian section, Apgar <7 at 5 min and admission to neonatal care were significantly associated with cerebral palsy (all p values<0.05). Among children born moderately or late preterm, small for gestational age, malformations, elective and emergency caesarian section and admission to neonatal care were all associated with cerebral palsy (all p values <0.05), whereas among children born very preterm no factors were significantly associated with the outcome (all p values>0.05). Conclusion: Our results support and strengthen previous findings on factors associated with cerebral palsy. The complete lack of significant associations among children born very preterm probably depends on to the small number of children with cerebral palsy in this group.